Pemberdayaan Masyarakat Desa Wee Paboba Dibidang Pangan Lokal, Pendidikan, Informasi Digital, Pertanian, Dan Sosial - Yuvensius Ramompas; Dewa Agung Hendrik; Melsandy Rambu Laki; Naomi Djara Lodu; Yovinianus Ndilu Ony; Gathan Syahputra Dinata; Adriani Ambu Kaka; Alfan Pindi Amah; Natalia Ndai Mbana; Agnes Rambu Nia Lepir; Osfred Umbu Djadji; Salmon Pandarangga; Firat Meiyasa; Nurbety Tarigan (AMMA : Jurnal Pengabdian Masyarakat, 2025)
Wee Paboba Village is located in North Wewewa District, SBD, has potential such as rich traditions and local knowledge especially in terms of land management and food utilization. However, the village community is still very dependent on traditional agricultural practices, the curriculum is less relevant to the local context, has not been able to utilize digital information for various purposes, limited knowledge in making organic fertilizer and animal feed, and limited access to information on social issues, especially in the school environment such as bullying. The purpose of this community service is to be able to identify and solve development problems in Wee Paboba Village, which is reflected in programs designed based on local needs and potential. Partners for this community service include village officials, housewives, farmer groups, livestock breeders, and students. The implementation method in this community service is descriptive qualitative. The results of this research in the field of local food, the village community now has new processed products with high economic value, in the field of education, children have a better interest in learning, in the field of digital information, village officials can manage information independently, in the field of agriculture, farmers and livestock breeders can save production costs, and in the social field, students better understand the importance of preventing bullying.